PELAKSANAAN LAYANAN PENEMPATAN DAN PENYALURAN OLEH GURU PEMBIMBING DALAM KEGIATAN PEGEMBANGAN DIRI EKSTRAKURIKULER DI SMA NEGERI 12 PADANG - Susanti, Ratih; Kasih, Fitria; Gusneli, Gusneli (Bimbingan dan Konseling, 2013)
These research initiation and background by implementation service on channel and placement with counselor in developing selves extracurricular action at Senior High School Negeri 12 Padang, these research is purposed for description been doing by counselor at Senior High School Negeri 12 Padang. These research is purposed for seeing how is assignment service program on channel and placement extracurricular action at Senior High School Negeri 12 Padang, with lay out research that is (1) Assignment and planning service program on channel and placement by doing counselor extracurricular action. (2) Implementation service program on channel and placement extracurricular action. (3) Evaluation/Assessment. These research face off research qualitative, the research consist of all informant counselor at Senior High School Negeri 12 Padang. The collecting data by doing with document and questioner upon implementation on channel and placement service by counselor extracurricular action. The resulting research have found out that is 1) assignment and planning service program on channel and placement extracurricular action have implemented with good category, 2) Implementation service program on channel and placement extracurricular act have implemented with good category, 3) Evaluation/assessment of implementation service program on channel and placement extracurricular act into good category.